2014
DOI: 10.1038/onc.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

AIP inactivation leads to pituitary tumorigenesis through defective Gαi-cAMP signaling

Abstract: The aryl hydrocarbon receptor interacting protein (AIP) is a tumor-suppressor gene underlying the pituitary adenoma predisposition. Thus far, the exact molecular mechanisms by which inactivated AIP exerts its tumor-promoting action have been unclear. To better understand the role of AIP in pituitary tumorigenesis, we performed gene expression microarray analysis to examine changes between Aip wild-type and knockout mouse embryonic fibroblast (MEF) cell lines. Transcriptional analyses implied that Aip deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 57 publications
2
92
1
4
Order By: Relevance
“…A second somatic mutation ('second hit') is necessary to loose the expression of the normal allele and to cause disease. When AIP activity is lost, it has been shown recently that the mechanism of tumorigenesis is related to the loss of inhibition of cAMP synthesis due to alteration in the function of inhibitory G-protein Gai2 [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A second somatic mutation ('second hit') is necessary to loose the expression of the normal allele and to cause disease. When AIP activity is lost, it has been shown recently that the mechanism of tumorigenesis is related to the loss of inhibition of cAMP synthesis due to alteration in the function of inhibitory G-protein Gai2 [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…AIP expression was associated to higher Gαi-2 and lower Ki67. In vitro Gαi-3 silencing revealed that AIP deficiency might lead to cAMP accumulation via Gαi-3, although its expression at protein level was not affected by the presence or absence of AIP (Tuominen et al 2015).…”
Section: The Role Of Aip and Zac1 In Ssa Response In Somatotrophinomasmentioning
confidence: 99%
“…AIP was found to be associated with Gα13, Gαq and possibly regulate the abundance of Gαi-2 (Nakata et al 2009, Tuominen et al 2015, Ritvonen et al 2017. These interactions could influence multiple signalling pathways, with the Gαi-cAMP pathway being especially relevant regarding somatotroph cells and somatostatin action (see section below).…”
Section: Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms of AIP-dependent pituitary tumorigenesis are elusive. Recent in vitro studies implicate the cAMP pathway, which seems to be activated by AIP deficiency (Formosa et al 2013, Tuominen et al 2014, but several lines of evidence also suggest the involvement of AhR. Most pathogenic AIP mutations alter the C-terminal region of the protein, particularly the last few amino acids required for AhR interaction (Bell et al 2000), resulting in loss of protein-protein interactions (Leontiou et al 2008, Morgan et al 2012.…”
Section: Introductionmentioning
confidence: 99%